Efeitos do procedimento de videomodelação no consumo de alimentos não preferidos por crianças com TEA - Guerra, Ana Carolina de Almeida (2023)
The presence of restricted patterns of behavior in autism spectrum disorder (ASD) can lead to food selectivity, which generates problematic consequences for the child’s nutritional and social status and behavior associated with meals. The present study aimed to investigate the effects of video modeling on the consumption of non-preferred foods in children with ASD. Two children aged between five and eight years old were selected as participants. A multiple baseline design was used, in four phases: baseline, intervention with video modeling, maintenance test, and generalization test. In the intervention, a single session was held per day, which began with the reproduction of a video in which the researcher presented the target foods (for each participant) on a plate, accompanied by the instruction: “It’s time to eat, give a bite". After the model consumed the five pieces of each non-preferred target food, each participant received the preferred food. If the participant placed a piece in their mouth, they were praised and given an item of their choice to handle. After consumption, the researcher requested and collected the item. Five trials were performed for each target food, and difficult behaviors were recorded as they occurred. The results demonstrated that, in the baseline, no participant consumed the non-preferred foods, while, in the video modeling phase, the consumption of the two non-preferred foods occurred for both participants. The results were maintained both in the maintenance test and the generalization test performed in the participants’ homes. The results suggest that video modeling was effective in increasing dietary consumption of non-preferred foods. The families of both participants reported that they introduced the changes into their routines and that the results were satisfactory, with maintenance of the repertoire